Micro Electro Discharge Machining of Nonconductive Ceramic: The Issue of Spalling - Yeakub Ali, Mohammad; Sabur, Abdus; Abdul Maleque, Md. (International Journal of Engineering and Technology, 2018)
Nonconductive ceramic materials are used in many engineering applications such as car brake, turbine blade, and hip-bone replacement because of its high dimensional accuracy, corrosion and wear resistant, and biocompatibility. These materials are usually processed with diamond grinding and limited laser applications such as cutting, drilling and scribing. Specific shapes and profiles are still difficult and costly to machine using these processes. Electrical discharge machining (EDM), extensively used for various shapes and profiles on conductive materials having minimum electrical conductivity of 0.10 S.cm-1. It is not directly applicable on nonconductive ceramic materials due to its very low electrical conductivity (
Keywords: Assisting electrode; Carbonic dielectric fluid; Material removal; Micro-EDM; Nonconductive ceramic; Pyrolytic carbon; Spalling.